As publicações da ANPAE e a trajetória do conhecimento em Administração da educação no Brasil - Maia, Graziela Zambao Abdian [UNESP] (My University, 2010)
This paper reports on the trajectory of knowledge in educational administration, as published by the Brazilian National Association of Educational Policy and Administration (ANPAE). It reviews four early booklets on school administration – Cadernos de Administração Escolar – published between 1961 and 1968, and selected issues of ANPAE´s journal – Revista Brasileira de Política e Administração da Educação – published between 1983 and 2000, under different categories, and analyses those classified under the concepts of administration and management. The author refers to conceptual limitations, but concedes that the publications present relevant contributions on the theoretical development of educational administration in Brazil.

O texto trata da trajetória da produção teórica em administração da educação veiculada pela Associação Nacional de Política e Administração da Educação (ANPAE). Examina os quatro primeiros textos dos Cadernos de Administração Escolar, publicados entre 1961 e 1968, e números selecionados da Revista Brasileira de Política e Administração da Educação, editados entre 1983-2000, cujos temas são organizados em categorias, e analisa as de administração e gestão. Apesar de limitações conceituais, a autora reconhece que as publicações oferecem contribuições relevantes para o desenvolvimento teórico em administração da educação no Brasil.

El objeto de este artículo es la trayectoria del conocimiento en administración de la educación, con base en trabajos publicados por la Asociación Nacional de Política y Administración de la Educación (ANPAE) del Brasil. El trabajo examina los cuatro primeros textos de los Cuadernos de Administración Escolar, publicados entre 1961 y 1968, y una selección de números de la Revista Brasileña de Política y Administración de la Educación (RBPAE), publicadas entre 1983 y 2000, organizados en categorías y analiza dos de ellas (1983-2000): administración y gestión. Pese a las limitaciones conceptuales, la autora reconoce que las publicaciones presentan contribuciones relevantes para el desarrollo teórico en la administración de la educación.